Homogeneous multigrid for HDG - Lu, Peipei; Rupp, Andreas; Kanschat, Guido (IMA journal of numerical analysis, 2022)
We introduce a multigrid method that is homogeneous in the sense that it uses the same hybridizable discontinuous Galerkin (HDG) discretization scheme for Poisson’s equation on all levels. In particular, we construct a stable injection operator and prove optimal convergence of the method under the assumption of elliptic regularity. Numerical experiments underline our analytical findings.
Online veröffentlicht am 19. Juli 2021
Gesehen am 10.01.2024